Analysis of individual-level and community-level effects on childhood undernutrition in Malawi - Peter Austin Morton Ntenda; Ying-Chih Chuang (Elsevier, 2018)
Background: Undernutrition is a major global public health problem among children under the age of 5 years. We aimed to untangle the effects of a wide range of individual- and community-level socioeconomic factors on the risks of childhood undernutrition in Malawi. Methods: We analyzed 6384 women-infant pairs from the 2004 and 2010 Malawi Demographic and Health Surveys (MDHSs). The undernutrition status was assessed by three domains of stunted (height-for-age), wasted (weight-for-height), and underweight (weight-for-age). We constructed generalized estimating equation logistic models to analyze associations of individual- and community-level characteristics with childhood undernutrition. Results: About 48.4% of the children were stunted, 4.5% were wasted, and 14.4% were underweight. At the individual level, the risk of childhood undernutrition was significantly higher in males, children with a small birth size, children with a diarrheal episode in the last 2 weeks, children that were a product of multiple births, children born to mothers with either a low socioeconomic status, or a poor education, or who were underweight, and children born in the year 2004. At community level, children born in communities with low and medium wealth, and in communities with low and medium female educational attainment were more likely to be undernourished. Unexpectedly, the maternal HIV status was not associated with childhood undernutrition at either the individual or community level. Conclusion: This study provides evidence of the importance of both individual- and community-level factors in determining childhood undernutrition. Interventions against childhood undernutrition should consider the various predictors discussed in this study in order to reduce undernutrition in children and contribute to their well-being. Key Words: childhood nutritional status, Malawi, stunting, underweight, wasting